Long-term predictors of myocardial infarction recurrence in patients with ST-elevation myocardial infarction treated with primary percutaneous coronary intervention. (25th November 2020) - Silverio, A; De Angelis, E; Cancro, F.P; Di Maio, M; Esposito, L; Romei, S; Citro, R; Ciccarelli, M; Vecchione, C; Galasso, G
Abstract: Background: Despite the implementation in the use of primary percutaneous coronary intervention (pPCI) and in secondary preventive measures, the risk of recurrence of myocardial infarction (MI) in patients who underwent ST-elevation myocardial infarction (STEMI) remains high. The prognostic role of old and emerging cardiovascular risk factors for MI recurrence, such as Lipoprotein(a) [Lp(a)] levels, in this very high-risk population is still not fully understood. Purpose: To identify the baseline predictors of MI recurrence in a cohort of patients admitted for STEMI and treated with pPCI. Methods: Single-center, observational, retrospective analysis of consecutive patients admitted for STEMI who underwent pPCI from February 2013 to April 2019 at our Insitution. Baseline demographic, clinical, echocardiographic and laboratory data were prospectively collected. Only patients with available Lp(a) values were included in the analysis. The study outcome was the recurrence of MI at three years follow-up. Univariable and multivariable Cox regression analysis was performed to identify the baseline variables correlated to the study outcome. Results: The study population included 560 patients (mean age = 60.6±13.7 years; 79.5% males). Hypertension was observed in 351 patients (62.7%), diabetes in 134 (23.9%), dyslipidemia in 266 (47.5%), smoking status in 316 (56.4%), history of coronary artery disease (CAD) in 76 (13.6%), prior MI in 69 (12.3%), prior PCI in 62 (11.1%). Multivessel disease (MVD) was reported in 211 (37.7%) cases. The infarct-related artery was the left anterior descending in 310 patients (55.4%), the right coronary artery in 179 (32.0%), the left circumflex 60 (10.7%) and the left main in 11 (2.0%). Total cholesterol mean value was 187.7±48.8 mg/dl; LDL cholesterol was 112.2±41.3 mg/dl and Lp(a) was 26.5±27.2 mg/dl. At three-year follow-up, MI occurred in 58 (10.4%) patients. At multivariable analysis, Lp(a) (HR 1.015 95% CI: 1.008–1.022 p<0.001) and MVD (HR 1.994; 95% CI 1.179–3.372 p=0.010) emerged as the only two independent predictors of MI recurrence up to three years. The Kaplan-Meier analysis showed a significantly lower survival free from MI in patients with Lp(a) ≥50 mg/dl as compared to the subgroups with levels ≥30 and <50 mg/dL, or <30 mg/dL (Log-Rank=0.001). Also, MVD was able to identify patients with significantly lower survival free from MI for up to three years (Log-Rank=0.004). The Kaplan-Meier analysis combining these two parameters identified patients with both MVD and Lp(a) ≥50 mg/dl as the highest risk cohort for MI recurrence up to three years (MI incidence rate=22.2%; Log-Rank=0.002). Conclusions: Among patients with STEMI who underwent pPCI, high Lp(a) level and MVD predict the recurrence of MI at long-term follow-up. Funding Acknowledgement: Type of funding source: None